Leibniz body, substance, monad - Garber, Daniel, 1949- (Oxford : Oxford University Press, 2009)
Daniel Garber presents a study of Leibniz's conception of the physical world, elucidating his puzzling metaphysics of monads, mind-like simple substances. Tracing the development of Leibniz's thought, Garber shows how dealing with problems about the physical world lead him to a world of animate creatures, and to a world of monads.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Leibniz, Gottfried Wilhelm, -- Freiherr von, -- 1646-1716.; Monadology